Antecedents and Consequences of Conspicuous Sport Consumption - Yukyoum Kim; Sun Hwan Hwang; Marshall Magnusen (Journal of Applied Sports Management, 2022)
Conspicuous consumption is when consumers acquire luxury goods and services to help publicly demonstrate their desired economic and social status. Even though conspicuous consumption can help individuals experience social distinction and a heightened sense of self-esteem, much still needs to be known about this occurrence in the context of sport. Accordingly, the focus of this study was to examine antecedents (i.e., Expertise and Self-esteem) and outcomes (i.e., Satisfaction and Subjective Well-being) of conspicuous consumption of upscale sport goods. An empirical study was conducted with cyclists (n = 393). The research model was analyzed using simultaneous equations analysis. Expertise was shown to have the largest impact on Satisfaction whereas Conspicuous Consumption had no impact on Satisfaction. Self-esteem was shown to have the largest influence on Subjective Well-being. Satisfaction also had a significant effect. However, the influence of Expertise on Subjective Well-being was not significant.
Keywords: Consumer Behavior; Expertise; Satisfaction; Sport; Well-being